Polish Messianic thought in Tadeusz Kroński’s analyses - Wawrzynowicz, Andrzej (Folia Philosophica, 2017)
Tadeusz Kroński (1907—1958) was one of the most influential representatives of Polish post-war Hegelianism. He was also regarded as the spiritual father of the Warsaw school of the history of ideas. In the 1950s, Kroński published historico-philosophical analyses focused on the ideas propounded by 19th century Polish Messianists of the inter-uprising period, presenting an outright negative view on the movement. Kroński does not see any significant features of theoretical continuity between the tradition of 19th century Polish Hegelianism, shaped by historical influences of the Romantic Messianic ideology (as formulated by Libelt and Cieszkowski), and his own philosophical position. The present study is aimed at a critical verification of Kroński’s analyses. It seeks to investigate the origins of the assumption regarding the fundamental discontinuity of both historical lines of development of Polish Hegelianism. Also, an attempt is made to delineate the actual extent of realization of the postulate of radical rejection of Messianic ideas.